Walking Pattern for Quadruped as Observer Robot. (May 2019) - Khomariah, Nuril Esti; Huda, Samsul
Abstract: This paper explains about the walking patterns of quadruped robots. This robot was made to be an observer robot. Therefore, being slick in movement is the main feature that must be owned by this robot. As a four-legged robot, the movement (forward, backward, shift left, shift right, rotate) requires an algorithm to control the synchronization movements of each leg. This algorithm consists of several poses (including the body, as well as all legs) and if arranged in sequence it will form a certain pattern of movement. Each leg has 3 DOF. The pose of each leg is represented in the cartesian coordinates (x, y, z axis), while the movement of each joint is represented in angular. It has solved using the inverse kinematics formula which is useful for converting leg coordinates into angular for each leg joint. By defining the walking pattern, the robot can more easily controlled by the direction and speed of its movement.